Ab initio study of hydrogen storage on metal-decorated GeC monolayers. (18th August 2021) - Arellano, Lucia Guadalupe; De Santiago, Francisco; Miranda, Álvaro; Pérez, Luis Antonio; Salazar, Fernando; Trejo, Alejandro; Nakamura, Jun; Cruz-Irisson, Miguel
Abstract: Bidimensional nanostructures have been proposed as hydrogen-storage systems owing to their large surface-to-volume ratios. Germanium carbide monolayers (GeC-MLs) can offer attractive opportunities for H2 adsorption compared to graphene. However, this possibility has not been explored in detail. In this work, the adsorption of H2 molecules on GeC-MLs decorated with alkali metal (AM) and alkaline earth metal (AEM) adatoms was investigated using the density functional theory. Results showed that the AM adatoms were chemisorbed on the GeC-ML, whereas AEM adatoms were physisorbed. The H2 molecules presented negligible adsorption energies on the weakly adsorbed AEM adatoms. Conversely, the AM adatoms improved the H2 adsorption, possibly due to a large charge transfer from the adatoms to the GeC-ML. The potassium-decorated GeC-ML exhibited the most optimal H2 storage capacity, adsorbing up to six molecules and with a lower possibility of forming metal clusters than the other studied cases. These results may aid in the development of new efficient hydrogen-storage materials. Graphical abstract: Image 1 Highlights: GeC monolayers were decorated with alkali and alkaline earth metal adatoms. Strong alkali metal—monolayer bond yields optimal H2 adsorption energies. Weak alkaline earth metal—monolayer bond yields negligible H2 adsorption energies. Li, Na and K adatoms can adsorb 3, 6 and 6H2 molecules, respectively. K-decorated GeC monolayers have unlikely adatom clusterization.